G109(P) Audit of management of children with recurrent headaches in paediatric neurology outpatient clinic at leeds teaching hospital. (27th April 2016) - Psychogiou, A; Ray, M
Abstract : Background and aims: Headaches are common in childhood and adolescence and a significant cause of school absence, poor school performance and reduction in quality of life. We audited the management of children who were referred for management of recurrent headaches in the paediatric neurology outpatient clinic at Leeds Teaching Hospital in accordance with NICE guidelines. Methods: We reviewed the case notes of 30 patients, who were referred to the paediatric neurology clinic for recurrent headaches, in the period of Sept 2014–Feb 2015. Children with secondary headaches were excluded. Data were collected as per BPNA Headache Audit subgroup proforma and children were diagnosed using the International Classification of headache disorders –II criteria. Results: Eighty percent of the cases came from general practice and 13% from regional general paediatricians. The mean age was 11.3 years and 63% were girls. Documentation of history taken and examination findings was satisfactory. Neuroimaging was performed in 19 of whom nearly half were imaged prior to referral. Incidental abnormalities were detected in 4 of them. Only half the children used of headache diaries appropriately. 67% were migraineurs and one fifth had chronic daily headaches. 7 children with migraines were offered preventive medications but the choice of drugs used varied amongst clinicians. Records of advice provided regarding non-pharmacological management was suboptimal. The documentation of explanation of risk of medication overuse headache to children was available only in 53.3%. Formal quality of life assessment in follow-up was unavailable. Conclusions: Migraines are common among those with primary headaches. Treatment practices vary widely even among specialists as evidence based guidance for pharmacological therapy is only available in those >12y. The use of headache diary is inadequate and needs encouragement. Making patients aware of medication overuse headaches and documentation of advice for non-pharmacological treatment warrants attention. Provision of written information about headaches disorders and support organisations is desirable.